Prevalence of Orthohantavirus-Reactive Antibodies in Humans and Peri-Domestic Rodents in Northern Ethiopia - Meheretu, Yonas; Granberg, Åsa; Berhane, Gebregiorgis; Khalil, Hussein; Lwande, Olivia Wesula; Mitiku, Mengistu; Welegerima, Kiros; Bellocq, Joëlle Goüy de; Bryja, Josef; Abreha, Hagos; Leirs, Herwig; Ecke, Frauke; et al. (Viruses, 2021)
In 2012, Tigray orthohantavirus was discovered in Ethiopia, but its seasonal infection in small mammals, and whether it poses a risk to humans was unknown. The occurrence of small mammals, rodents and shrews, in human inhabitations in northern Ethiopia is affected by season and presence of stone bunds. We sampled small mammals in two seasons from low- and high-density stone bund fields adjacent to houses and community-protected semi-natural habitats in Atsbi and Hagere Selam, where Tigray orthohantavirus was first discovered. We collected blood samples from both small mammals and residents using filter paper. The presence of orthohantavirus-reactive antibodies in blood was then analyzed using immunofluorescence assay (human samples) and enzyme linked immunosorbent assays (small mammal samples) with Puumala orthohantavirus as antigen. Viral RNA was detected by RT-PCR using small mammal blood samples. Total orthohantavirus prevalence (antibodies or virus RNA) in the small mammals was 3.37%. The positive animals were three Stenocephalemys albipes rats (prevalence in this species = 13.04%). The low prevalence made it impossible to determine whether season and stone bunds were associated with orthohantavirus prevalence in the small mammals. In humans, we report the first detection of orthohantavirus-reactive IgG antibodies in Ethiopia (seroprevalence = 5.26%). S. albipes lives in close proximity to humans, likely increasing the risk of zoonotic transmission.
Keywords: risk factors; Ethiopia; RNA virová; Disease Reservoirs; Humans; rural community; orthohantavirus; imunoglobulin G; prevalence; zdroje nemoci; rizikové faktory; Female; rodents; krysa rodu Rattus; lidé; zvířata; Hantavirus; Hantavirus Infections; Etiopie; venkovské obyvatelstvo; ženské pohlaví; Male; hantavirové infekce; Cross-Sectional Studies; RNA, Viral; protilátky virové; Prevalence; Rats; Rural Population; Antibodies, Viral; Animals; mužské pohlaví; Immunoglobulin G; průřezové studie; Orthohantavirus; Risk Factors